Thermal perceptions, preferences and adaptive behaviours of occupants of nursing homes. (15th March 2018) - Tartarini, Federico; Cooper, Paul; Fleming, Richard
Abstract: While the rapid increase in the fraction of people aged over 65 is driving a substantial increase in the number of people living in nursing homes, there has been very limited previous research carried out on how residents of nursing homes perceive their thermal environment and there is a lack of thermal comfort guidelines for the aged care sector. This article reports on a study to investigate thermal perceptions, preferences and adaptive behaviours of occupants in five nursing homes. Participants were asked to complete a questionnaire while local environmental parameters were monitored in their near proximity using portable equipment. Not all the facilities in the study provided a thermally comfortable environment for occupants at all times, and indoor air temperatures were found to range between 17.2 °C and 31.6 °C over the course of the study. As a result, participants adopted a range of adaptive behaviours to compensate for unsatisfactory thermal comfort conditions, such as adjustment of their clothing and the use of ceiling and portable fans in summer. Residents were more tolerant of temperature variations than staff or visitors and both the estimated neutral and preferred temperatures were higher for residents than for non-residents. The findings of this study are likely to have practical implications for all the stakeholders in the aged care sector. The results may also be used to inform the design of new facilities and the assessment of thermal comfort conditions in existing nursing homes. Highlights: Participants effectively adjusted their clothing insulation and local air velocity. Total clothing insulation varied as function of age, metabolic rate and BMI. The neutral temperature for residents in summer was higher than for non-residents. The estimated comfort range for residents was 19.1–26.2 °C. The PMV was not a precise predictor of the personal thermal state of occupants.